2021
DOI: 10.1007/s40615-021-01003-w
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Patient-Physician Racial Concordance Associated with Improved Healthcare Use and Lower Healthcare Expenditures in Minority Populations

Abstract: Publisher's Note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is supported by previous research which found racial concordance to be positively related with patient satisfaction, improved communication and better health outcomes. 26 27 However, these studies are based in the USA, did not include T2D programmes and there was no differentiation between ‘Asian’ participants. 26–28 By contrast, for some participants, cultural competence was more important than ethnic matching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by previous research which found racial concordance to be positively related with patient satisfaction, improved communication and better health outcomes. 26 27 However, these studies are based in the USA, did not include T2D programmes and there was no differentiation between ‘Asian’ participants. 26–28 By contrast, for some participants, cultural competence was more important than ethnic matching.…”
Section: Discussionmentioning
confidence: 99%
“… 26 27 However, these studies are based in the USA, did not include T2D programmes and there was no differentiation between ‘Asian’ participants. 26–28 By contrast, for some participants, cultural competence was more important than ethnic matching. Different views on ethnic matching are supported in the literature, including a lack of clarity in research for cultural matching, instead evidence suggests more important than ethnic matching is cultural competency of the service provider.…”
Section: Discussionmentioning
confidence: 99%
“…Diversity, equity, and inclusion across all roles in health care teams promote high-quality, cost-effective, and patient-centered care [ 26 ]. In the long term, community-specific concordance between patients and health care providers may help achieve equitable health outcomes [ 27 , 28 ]. Institutional efforts in the recruitment and retention of diverse faculty and students can help achieve this goal [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%